3D Printed tandem X-Ray detector with halide perovskite-polymer composite semiconductor absorber - Haoran Li; Xin Shan; Shiran Bao; Sean Psulkowski; Wei Guo; Tarik Dickens; Zhibin Yu (Advanced Manufacturing)
A semiconductor-polymer composite was developed in this work consisting of inorganic halide perovskite (CsPbBr3) crystals embedded in polylactic acid (PLA) matrix. The composite exhibits the essential semiconductor properties of CsPbBr3 and the easy processability of PLA, enabling 3D printed tandem X-ray detectors. The tandem detectors demonstrated a sensitivity of 383 μC Gyair-1 cm-2 when four layers and total 600 µm thick CsPbBr3-PLA were printed. This sensitivity is 23X of single-layer detectors with same absorber thickness. The result indicates that 3D printed tandem detectors can overcome the X-ray absorption vs. charge carrier collection tradeoff in conventional single-layer detectors towards high performance radiation detection.